The Impact Of Tax Policy On Economic Growth In Syrian Arab Republic - اسماعيل, عصام; منصور, مضر (Latakia University Journal - Economic and Legal Sciences Series, 2022)
Tax policy is one of the important financial and economic tools and a main source of public revenue, which enables the state to achieve its economic and social goals, and increasing the rate of economic growth is at the forefront of these goals because of its positive repercussions on all economic and social indicators. This study aims to examine the reality of tax policy and its structure, the changes that occurred in it, and measure its impact on economic growth in Syria, where the descriptive and analytical approach was used in studying the different types of taxes and clarifying their impact on the rate of economic growth during the study period, and measuring the short-term and long-term relationship between Taxes and economic growth, through the use of the econometrics methods for studying data in the Syrian Arab Republic between the years (1980 - 2010), and reaching a set of conclusion, the most important of which is the existence of a structural defect in the structure of taxes and their classification between direct and indirect taxes. The study also found a long-term relationship between taxes on capital, taxes on expenditures and GDP, which is a direct and moral relationship, while the relationship was not significant. Between GDP and both income taxes and customs taxes, and the positive and significant relationship between the value of GDP and the value of the slowed GDP, and this indicates the presence of a part of the changes in the value of GDP that are not explained by the studied independent variables